(untitled) (Veterinária Notícias, 2021)
The lymphatic system is generally responsible for defending the body as it protects the body against exogenous and endogenous macromolecules as well as invading microorganisms. Inflammatory alterations, of infectious or toxic origin, are frequently seen in the lymph nodes. Lymphadenitis may be associated with drainage of a certain inflamed area of the body, may result from primary lymph node injury or may occur as part of a multicenter disease. Caseous lymphadenitis is an important disease in goats and sheep, characterized by the formation of abscesses in superficial lymph nodes and, less frequently, in internal lymph nodes and organs, considered chronic, debilitating and infectious. Anatomical variations are morphological differences between organisms of the same species. In this context, anatomical variations related to superficial lymph nodes may be of great importance in sheep and goats production.